Synchronous and metachronous bilateral germ cell tumours of the testis - Berkmen, Ferhat (Radiology and oncology (Ljubljana), 2000)
Background. We reported fourteen patients with bilateral testicular tumors, and discussed the need for contralateral testicular biopsy during orchiectomy to detect carcinoma in situ (CIS). Patients and methods. Fourteen patients with bilateral testicular tumours were reviewed in order to establish the incidence, histologic findings, predisposing factors, interval between the development of two primaries, type of treatment administered and the overall outcome. Results. Bilateral tumors were identified fourteen times between 1984and 1996. The tumours occurred simultaneously in five patients, and a contralateral malignancy developed in the others after a time ranging between 6 and 107 months. The most frequent histologic diagnosis was seminoma and was confirmed in 10 cases. Four patients had a history of undescended testis. One patient also had persistent muellerian duct syndrome. All patients were initially treated with radical orchiectomy. According to their stage, all patients were treated with radiotherapy and/or chemotherapy. Four patients died in the period between 6 and 33 months after the diagnosis. The remaining 10 are still alive with, no evidence of disease. Conclusions. The second tumoris diagnosed more often due to prolonged follow-up examinations; periodicself-examination by patients; ultrasonography of the testis; tumour markers AFP and beta-HCG and a contralateral testicular biopsy during orchiectomy. CIS of the contralateral testis evolves into invasive cancer in probably most of the patient germ cell tumours and usually cured by radiotherapy. (Abstract truncated at 2000 characters.)
Keywords: Carcinoma in situ; diagnostika; Drug therapy; Germinoma; Orchiectomy; Pathology; Testicular neoplasms; testisi; Therapy; tumorji